CARACTERIZAÇÃO HIDROGEOLÓGICA DO DISTRITO DE ICOARACI - Oliveira, Josafá Ribeiro de; Conceição, Adib Leal da; Centeno Júnior, Feliberto M.; Pontes, Manfredo Ximenes; Schalken, Chales George Pereira das S. (Águas Subterrâneas, 2001)
Resumo não disponível.